Malignant melanoma metastasis in the gallbladder. A case report of an unusual metastatic site. (2020) - Hess, Gabriel Fridolin; Glatz, Katharina; Rothschild, Sacha I.; Kollmar, Otto; Soysal, Savas Deniz; Boll, Daniel T.; Droeser, Raoul André; Mechera, Robert
Highlights: Malignant melanoma metastasis into the gallbladder is a rare issue. Surgical treatment in a metastasized situation has to be carefully evaluated. Prevention of possible biliary complications is of significant importance. Abstract: Introduction: Malignant melanoma is a neoplasia with the ability to metastasize to all organs. Most frequently, metastases derives from a skin primary. A solitary metastasis in the gallbladder is rarely mentioned in current literature. Presentation of case: We present the case of a 62-year-old female patient with the unusual metastatic spread of malignant melanoma into the gallbladder. The lesion was detected during routine follow up appointment six years after the initial surgical and radio-chemotherapeutic treatment of a malignant melanoma on the back. Following multidisciplinary team meeting, it was decided to perform a laparoscopic cholecystectomy to remove the gallbladder metastasis. Discussion: New occurrence of a melanoma metastasis in the gallbladder is extremely rare, especially in stable disease. The therapeutical concept must be discussed extensively in the present of this metastasized tumor. Conclusion: In otherwise stable disease, palliative surgery for metastasis in the gallbladder is a possible option to prevent biliary complications. In a palliative setting always weigh up the risks and benefits while maintaining the quality of life.